A guide to Christian spiritual formation : how scripture, spirit, community, and mission shape our souls - Howard, Evan B., 1955- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2018)
Grounded in careful biblical scholarship, this volume provides a holistic, accessible, and informed introduction to Christian spiritual formation, written from a broadly evangelical perspective. Evan Howard, a noted authority on Christian spirituality, joins Scripture with themes of community, spirit, formation, and mission in a single integrative guide. A Guide to Christian Spiritual Formation includes helpful features such as figures, charts, chapter overviews, and formation-focused questions. Its evangelical-ecumenical and global perspectives will appeal to a wide audience. --! From publisher's description.
The basics -- Christian spiritual formation -- The story of Christian spiritual formation -- The elements -- The fullness and aims of Christian spiritual formation -- The contexts and agents of Christian spiritual formation -- The process of transformation and the task of formation -- The means of Christian spiritual formation -- The practice -- Formed into prayer -- Formed together -- Formed in thinking, feeling, and acting -- Formed into mission -- Discerning formation -- The ministry -- The ministry of Christian spiritual formation -- My personal history of spiritual formation.
Includes bibliographical references and index.
Keywords: Spiritual formation; Spiritual formation